Attaining the 2030 sustainable development goal of climate action - Birdthistle, Naomi; Hales, Rob (Emerald Publishing Limited, 2022)
Attaining the 2030 Sustainable Development Goal of Climate Action focuses on Sustainable Development Goal number thirteen (SDG13): urgent action to combat climate change and its impacts. Examining family businesses in Germany, Australia, the United States and the United Kingdom, each case study presents a unique perspective from their respective countries of how SDG13 translates into strategy, culture, and the practice of doing business, providing insights and key takeaways into how family businesses can play a role in combatting climate change. The United Nations' (UN) Sustainable Development Goals (SDGs) are 17 Goals pledged by 193 nations in 2015 which would help engender an improved, fairer, and more sustainable world - one in which 'no one is left behind'. The SDGs are a call to action, to develop innovative solutions to the most complex, societal, and environmental global challenges. In Family Businesses on a Mission, series editors Naomi Birdthistle and Rob Hales bring together international case studies to illustrate how family businesses can attain the UN 2030 SDGs. Accessible to those working in the field beyond academia - such as family business practitioners, family business owners, government and policymakers, members of NGOs, business associations and philanthropic centres - the book series equally appeals to those with a general interest in entrepreneurship and business.
Keywords: Sustainable Development Goals.; Family-owned business enterprises -- Environmental aspects.; Climate change mitigation.; Sustainable development.; Business & Economics -- Development -- Sustainable Development.; Business & the environment, 'Green' approaches to business.; elektronické knihy; electronic books